Chlorotoxin-functionalized mesoporous silica nanoparticles for pH-responsive paclitaxel delivery to Glioblastoma multiforme - Mirjana Mundžić; Amelia Ultimo; Minja Mladenović; Aleksandra Pavlović; Oliviero L. Gobbo; Eduardo Ruiz-Hernandez; Maria Jose Santos-Martinez; Nikola Ž. Knežević (Heliyon)
Glioblastoma multiforme (GBM) is a highly aggressive brain cancer associated with poor survival rates. We developed novel mesoporous silica nanoparticles (MSNs)-based nanocarriers for pH-responsive delivery of a therapeutic drug Paclitaxel (PTX) to GBM tumor cells. The pores of MSNs are loaded with PTX, which is retained by β-cyclodextrin (CD) moieties covalently linked to the pore entrances through a hydrazone linkage, which is cleavable in weakly acidic environment. Furthermore, we utilized a host-guest interaction between the adamantane and capping CD moieties to further functionalize the surface with a potential glioma-targeting oligopeptide chlorotoxin (CHX). In vitro studies in the U87 GBM cell line show decreased uptake, but increased toxicity of CHX-modified nanoparticles compared to CHX-free nanoparticles. The obtained results are promising toward development of advanced drug nanocarriers, which may target the overexpressed receptors in cancer tissues and utilize their weakly acidic environment for triggering the drug release, potentially leading to more efficient cancer treatments.